2013
DOI: 10.1371/journal.pone.0051815
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change or Urbanization? Impacts on a Traditional Coffee Production System in East Africa over the Last 80 Years

Abstract: Global environmental changes (GEC) such as climate change (CC) and climate variability have serious impacts in the tropics, particularly in Africa. These are compounded by changes in land use/land cover, which in turn are driven mainly by economic and population growth, and urbanization. These factors create a feedback loop, which affects ecosystems and particularly ecosystem services, for example plant-insect interactions, and by consequence agricultural productivity. We studied effects of GEC at a local leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
56
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 52 publications
5
56
1
3
Order By: Relevance
“…Our work supports recent papers suggesting that provision of shade trees is likely to be an effective way of managing coffee berry borers (Teodoro et al 2008;Jaramillo et al 2009Jaramillo et al , 2011Jaramillo et al 2013;Karp et al 2013), but contradicts studies that either failed to show an effect of shade (Soto-Pinto et al 2002), or indicated that excessive shade may increase borer problems (Willey 1975). Together, this suggests that shade tree provision is an effective approach to manage coffee berry borers in many situations but that this may not be the case at all locations or shade levels.…”
Section: Coffee Berry Borersupporting
confidence: 76%
See 1 more Smart Citation
“…Our work supports recent papers suggesting that provision of shade trees is likely to be an effective way of managing coffee berry borers (Teodoro et al 2008;Jaramillo et al 2009Jaramillo et al , 2011Jaramillo et al 2013;Karp et al 2013), but contradicts studies that either failed to show an effect of shade (Soto-Pinto et al 2002), or indicated that excessive shade may increase borer problems (Willey 1975). Together, this suggests that shade tree provision is an effective approach to manage coffee berry borers in many situations but that this may not be the case at all locations or shade levels.…”
Section: Coffee Berry Borersupporting
confidence: 76%
“…It has been shown that biological control of the coffee berry borer is more effective in forested coffee plantations (Karp et al 2013;Railsback and Johnson 2013), and that abandoned coffee plantations may have lower coffee berry borer abundances compared to managed coffee agroforests with lower levels of shade (Teodoro et al 2008). Recently, Jaramillo et al (2013) found higher coffee berry borer infestations in a sunexposed coffee plantation compared to a shaded one. Other studies, however, failed to show an influence of shade on coffee berry borers (Soto-Pinto et al 2002), and some older observations even indicate that excessive shade may increase coffee berry borer attack rates (Willey 1975).…”
Section: Introductionmentioning
confidence: 99%
“…Annual production and share of coffee in the County's GDP have significantly declined. Climate change is one of the major factors affecting coffee production: it induces the coffee trees to dry, increases the incidence of coffee pests and diseases (Jaramillo et al 2013), depresses tree growth and provokes coffee flower abortion (Thuku 2013). Future projections (Laderach et al 2011) indicate the optimum coffee-producing zone will shift still higher to the 1680-1800 masl range to compensate for expected temperature increase in the lower altitude ranges (Craparo et al 2015;Laderach 2011).…”
Section: Profile Of the Study Areamentioning
confidence: 99%
“…However, rainfall reduces from time to time while hot periods become more common. As a result, coffee plants tend to dry, while pests and diseases develop, affecting many coffee growers (Jaramillo et al, 2013).…”
Section: The Murang'a Case Study In Central Kenyamentioning
confidence: 99%
See 1 more Smart Citation